2002
DOI: 10.1002/nur.10019
|View full text |Cite
|
Sign up to set email alerts
|

Waiting: The experience of persons in a critical care waiting room

Abstract: The purposes of this study were to discover the essences of the experience of waiting, to provide new knowledge about what it is like to wait, and to contribute to nursing knowledge. Participants were 12 persons who were family members or friends of persons in an adult critical care unit. The Parse research method was used to answer the research question: What is the structure of the lived experience of waiting? The central ®nding of this study was this structure: The lived experience of waiting is a vigilant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 17 publications
2
97
0
1
Order By: Relevance
“…Family members left alone in a waiting room may experience ''the emotional hell of waiting'' [37]. With no or fewer waiting rooms, next of kin may be admitted sooner to the patient's bed.…”
Section: Discussionmentioning
confidence: 99%
“…Family members left alone in a waiting room may experience ''the emotional hell of waiting'' [37]. With no or fewer waiting rooms, next of kin may be admitted sooner to the patient's bed.…”
Section: Discussionmentioning
confidence: 99%
“…Being in close proximity provided comfort in knowing one could ‘peek in’ at their relative and receive information through face‐to‐face communication at any time. Bournes and Mitchell (2002) found that family members talked about ‘not wanting to go too far away – just in case’ and ‘being there to see that he is still breathing’.…”
Section: Discussionmentioning
confidence: 99%
“…The core concept wavering irresolutely with discerning ponderings was not explicitly described in the extant literature on uncertainty, unsureness, and feeling unsure, but was consistent with some ideas discussed by various authors (Bournes & Mitchell, 2002;Bunkers, 2007;Hilton, 1988;Mishel, 1990;Morse & Penrod, 1999;Morrow, 2006;Penrod, 2007).…”
Section: Wavering Irresolutely With Discerning Ponderingsmentioning
confidence: 60%